Thermally-activated flow in nominally binary Al–Mg alloys. (15th January 2016) - Leyson, G.P.M.; Curtin, W.A.
Abstract: The temperature-dependent flow behavior in nominally binary Al–Mg alloys measured recently (Jobba et al., 2015; Niewczas et al., 2015) is interpreted in the context of a parameter-free solute strengthening model. The recent measurements show consistently higher strengths as compared to literature data on true binary Al–Mg alloys, which is attributed to the presence of Fe in the nominally binary Al–Mg. Using the Fe concentration as a single fitting parameter, the model predictions for the newer materials when treated as Al–Mg–(Fe) alloys agree with experiments to the same degree as obtained for the true binary Al–Mg. The model then predicts the activation volume in good agreement with experimental trends.